2020
DOI: 10.1177/0899764020911203
|View full text |Cite
|
Sign up to set email alerts
|

When Public Recognition Inhibits Prosocial Behavior: The Case of Charitable Giving

Abstract: Commonly regarded as an important driver of donation behavior, public recognition also can reduce donations. With three studies, this research manipulates whether donors receive public, private, imposed, or optional forms of recognition; the results show that the influence of recognition on the decision to donate is moderated by donors’ need for social approval. Whereas public recognition improves charitable giving among people with higher need for approval, imposing recognition reduces donations among people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…Future research should continue to inform the nonprofit community of changes relating to the perception of the nonprofit whistleblowing website option. In addition, research has shown that prosocial behavior is reduced for those with lower recognition need (Dennis et al, 2020). Given the whistleblower protection laws focus on for-profit public companies, future regulation to protect nonprofit whistleblowers may increase such behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should continue to inform the nonprofit community of changes relating to the perception of the nonprofit whistleblowing website option. In addition, research has shown that prosocial behavior is reduced for those with lower recognition need (Dennis et al, 2020). Given the whistleblower protection laws focus on for-profit public companies, future regulation to protect nonprofit whistleblowers may increase such behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent meta-analysis found that although there is a small and statistically significant positive effect of observability on prosocial behaviour, the effect is highly heterogeneous and context-dependent (164). For example, public recognition can decrease people's willingness to donate blood (165) or to donate to charity (166)(167)(168). Experimental studies have shown that individuals feel uncomfortable when they learn that they are morally superior to their peers (169) or when their moral actions are highlighted to others (170) and these negative feelings might prompt individuals to hide their good deeds from others.…”
Section: Reputation Management Strategies In Humansmentioning
confidence: 99%
“…Public recognition has been regarded as a facilitator for charitable giving (Denis et al, 2020) and thus it has become one of the most common approaches applied by charitable organizations to increase donations (Lucas, 2017). Charitable public recognition is defined as "occurring when the donor's donation decision will be made known to others" (Simpson et al, 2018) and "offering supporters the chance to visibly show to their peers that they have done a good deed" (Lucas, 2017).…”
Section: Public/private Recognition For Charitable Givingmentioning
confidence: 99%
“…Intuitively, public recognition provides individuals with a motivational drive of social approval to engage in charitable giving, and thus charitable organizations are increasingly adopting public recognition as a means to encourage charitable giving (Bekkers & Wiepking, 2011). However, some recent research suggests that public recognition is not necessarily superior to private recognition in the practice of charitable giving (Denis et al, 2020;Simpson et al, 2018). For example, if the donation is inspired by intrinsic factors such as guilt or personal values, public recognition may backfire (Denis et al, 2020;Simpson et al, 2018).…”
Section: Public/private Recognition For Charitable Givingmentioning
confidence: 99%
See 1 more Smart Citation